2021
DOI: 10.15252/embj.2021108053
|View full text |Cite
|
Sign up to set email alerts
|

TIMELESS‐TIPIN and UBXN‐3 promote replisome disassembly during DNA replication termination in Caenorhabditis elegans

Abstract: The eukaryotic replisome is rapidly disassembled during DNA replication termination. In metazoa, the cullin‐RING ubiquitin ligase CUL‐2LRR‐1 drives ubiquitylation of the CMG helicase, leading to replisome disassembly by the p97/CDC‐48 “unfoldase”. Here, we combine in vitro reconstitution with in vivo studies in Caenorhabditis elegans embryos, to show that the replisome‐associated TIMELESS‐TIPIN complex is required for CUL‐2LRR‐1 recruitment and efficient CMG helicase ubiquitylation. Aided by TIMELESS‐TIPIN, CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 63 publications
4
36
0
Order By: Relevance
“…The pleckstrin homology domain interacts with the ZnF domains of MCM2 and MCM6, parental dsDNA and the N-terminal region of the TIMELESS α-solenoid (Extended Data Fig. 10c, d ), consistent with the reported role for TIMELESS–TIPIN in recruiting CUL2 LRR1 to the replisome in Caenorhabditis elegans 30 . The LRR domain comprises seven canonical and two irregular LRR motifs and forms a shallow arc, reaching from the parental dsDNA to the N-tier face of MCM3 and MCM5 (Fig.…”
Section: Human Replisome–cul2 Lrr1 Structuresupporting
confidence: 81%
See 1 more Smart Citation
“…The pleckstrin homology domain interacts with the ZnF domains of MCM2 and MCM6, parental dsDNA and the N-terminal region of the TIMELESS α-solenoid (Extended Data Fig. 10c, d ), consistent with the reported role for TIMELESS–TIPIN in recruiting CUL2 LRR1 to the replisome in Caenorhabditis elegans 30 . The LRR domain comprises seven canonical and two irregular LRR motifs and forms a shallow arc, reaching from the parental dsDNA to the N-tier face of MCM3 and MCM5 (Fig.…”
Section: Human Replisome–cul2 Lrr1 Structuresupporting
confidence: 81%
“…Furthermore, like Cdc53, CUL2 displays considerable conformational variability, which is probably important for the conjugation of long polyubiquitin chains onto MCM7 (refs. 8 , 30 ) (Extended Data Figs. 5a , 10b ).…”
Section: Human Replisome–cul2 Lrr1 Structurementioning
confidence: 99%
“…In reconstituted reactions analogous to those described above, we found that a carboxy-terminal fragment of UBXN-3 comprising the coiled-coil and UBX domains was sufficient to promote the disassembly of ubiquitylated CMG helicase by C. elegans CDC-48_UFD-1_NPL-4 (Figure 3figure supplement 2A-B, UBXN-3-∆435). Moreover, the UBX domain was essential for UBXN-3 to stimulate CDC-48_UFD-1_NPL-4 (Figure 3-figure supplement 2A-B, UBXN-3-∆UBX), as reported recently (Xia, Fujisawa, Deegan, Sonneville, & Labib, 2021), but was insufficient in the absence of the coiled-coil domain (Figure 3-figure supplement 2A-B, UBXN-3-∆527).…”
Section: Ufd1-npl4supporting
confidence: 74%
“…If we take the N-terminus of the LRR domain as a pivot around which the PH domain can rotate on its flexible tether, the PH domain could potentially interact with DNA, the fork protection complex, And-1, CMG or a combination of some of these structures (Figure 5B ). An interaction with the fork protection complex would be consistent with a stimulatory role for Tipin and Timeless orthologs in the ubiquitylation of CMG by C. elegans CUL-2 LRR-1 ( 47 ). On the other hand, an interaction with And-1 would fit observations that the TPR domain of Dia2 directly interacts with Ctf4, the yeast ortholog of And-1 ( 46 , 48 ).…”
Section: Discussionmentioning
confidence: 71%